Cullin 3, a cellular scripter of the non-proteolytic ubiquitin code - Jerabkova, Katerina; Sumara, Izabela (Seminars in cell & developmental biology, 2019)
Cullin-RING ubiquitin ligases (CRLs) represent the largest family of E3 ubiquitin ligases that control most if not all cellular processes. In CUL3-based CRLs, the substrate specificity is conferred by the interaction with one of around 183 existing BTB proteins, implying a broad spectrum of possible ubiquitylation signals and possible direct ubiquitylation substrates. Indeed, CUL3-based E3-ligases can catalyze various proteolytic and non-proteolytic ubiquitin signals regulating many physiological and pathophysiological states. Here, we discuss the recent studies focusing on the non-proteolytic CUL3-based signaling in mammalian cells, which emerge as important pathways during cell division, embryonic development as well as other biological processes. Mechanistically, non-proteolytic ubiquitin signals generated by CUL3 E3-ligases often regulate substrates' interactions with other downstream factors or their subcellular localization. Existing data also demonstrate an interplay with the proteolytic ubiquitylation catalyzed on the same substrates by different E3-ligases or by the same CUL3-BTB CRL3s on different substrates. In future, a deeper understanding of the upstream spatiotemporal regulatory mechanisms will help to dissect this fascinating CUL3 ubiquitin code.
Keywords: ubikvitin; Ubiquitin; Humans; Substrates; Cullin Proteins; proteolýza; Cell division; Cullin 3; Non-proteolytic signaling; Ubiquitin code; Development; lidé; kulinové proteiny; Proteolysis